Implementation Analysis of Changes in Building Use Rights for Residential Houses Encumbered with Mortgage into Ownership - Ahmad Rizal Qomaruddin; Bambang Tri Bawono; Widayati Widayati; Denny Suwondo (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to analyze: 1) The implementation of the change in Building Use Rights on land for residential houses to become Ownership Rights that are encumbered with Mortgage Rights. 2) The legal consequences of changing the Right to Build on land for residential homes into Ownership Right which is encumbered with Mortgage Rights. This study uses an empirical juridical approach, namely an approach by reviewing the laws and regulations relating to the issues to be discussed, and also a field approach to obtain information as supporting material. The specification of this research is descriptive analytical, which describes the applicable laws and regulations associated with legal theories and practices of implementing positive law regarding these problems. Based on the results of the study obtained the results: 1) The implementation of the change of building use rights on land for residential houses into ownership rights that are encumbered with mortgage rights, namely starting from the Applicant must first obtain written permission from the Bank holding mortgage rights, that there will be changes to rights, namely building use rights will be upgraded to property rights. After receiving from the bank, the applicant or his proxies submits a request to change the Right to Build on the land for a residential house that is being encumbered with a Mortgage into a Property Right at the Land Office of Semarang City by bringing all the requirements, after verification, the application file is forwarded to the data processing officer, the abolition of the Building Use Right and the abolition of the Mortgage Right concerned in the land book and certificate as well as other general registers as well as recording the Ownership Rights on the land of the former Building Use Rights by mentioning the decision on which the ownership rights were based. 2) The legal consequence of changing the Right to Build on land for residential homes into Ownership Right which is encumbered with Mortgage Rights is the nullification of the right to use the building to become property rights. However, the abolition of the right to use the building does not result in the abolition of the guaranteed debt. This is in accordance with the nature of the agreement for granting Mortgage, namely as a complementary agreement (accessoir), Article 10 paragraph (1) UUHT.